2017
DOI: 10.1039/c6en00630b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a novel anticorrosion engineered nanomaterial on the bivalve Ruditapes philippinarum

Abstract: Metallic corrosion is an unsolved problem that has been minimized through the application of specialized coatings containing corrosion inhibitors, such as 2-mercaptobenzothiazole (MBT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 72 publications
6
12
0
Order By: Relevance
“…The absence of major reflections assigned to the nitrate inside the LDH, guarantees the replacement of intercalating anions. The basal spacing determined for Zn2Al(OH)6-MBT is in excellent agreement with the range of values, 1.67 nm -1.72 nm, that are found in the literature for dried samples of this material (Poznyak et al, 2009;Tedim et al, 2010;Carneiro et al, 2015;Serdechnova et al, 2016;Stimpfling et al, 2016;Martins et al, 2017;Abdolah Zadeh et al, 2018). Note, however, that the present results for Zn2Al(OH)6-MBT LDH differ from those reported by Dong et al (Dong et al, 2014) where an interlayer of 1.34 nm was determined, probably because of an incomplete substitution of NO3by MBT -.…”
Section: Analysis Of the Experimental Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The absence of major reflections assigned to the nitrate inside the LDH, guarantees the replacement of intercalating anions. The basal spacing determined for Zn2Al(OH)6-MBT is in excellent agreement with the range of values, 1.67 nm -1.72 nm, that are found in the literature for dried samples of this material (Poznyak et al, 2009;Tedim et al, 2010;Carneiro et al, 2015;Serdechnova et al, 2016;Stimpfling et al, 2016;Martins et al, 2017;Abdolah Zadeh et al, 2018). Note, however, that the present results for Zn2Al(OH)6-MBT LDH differ from those reported by Dong et al (Dong et al, 2014) where an interlayer of 1.34 nm was determined, probably because of an incomplete substitution of NO3by MBT -.…”
Section: Analysis Of the Experimental Resultssupporting
confidence: 88%
“…The distance between the cationic layers of Zn2Al(OH)6-MBT determined from the analysis of the XRD is in the range 1.66 -1.68 nm (Table 2), in agreement with the 1.67 nm -1.72 nm interval from the literature (Poznyak et al, 2009;Tedim et al, 2010;Carneiro et al, 2015;Serdechnova et al, 2016;Stimpfling et al, 2016;Martins et al, 2017;Abdolah Zadeh et al, 2018). The inspection of Figure 5 shows that the calculated structure with an interlayer spacing of ~1.7 nm is found only when ~ 4.5 water molecules per anionic MBT (run16) are in the interlayer spaces.…”
Section: The Role Of Water Inside the Ldh Galleriessupporting
confidence: 87%
“…The high efficacy of LDH-ZnPT on mussels may imply its specific mode of activity, mostly related to the biocide [25,34]. Consequently, the findings of the present study indicate that the presence of LDH-ZnPT may contribute to the release of ionized PT from ZnPT and Zn ++ from the ZnPT and LDH structure, and therefore explains the lethality caused by LDH-ZnPT on mussels.…”
Section: Znpt and Cupt Loaded Nanomaterialsmentioning
confidence: 72%
“…In the present study, the unloaded Zn-Al LDH exhibited lower mortality, which indicates it as an ideal carrier for active compounds. Similarly, Avelelas et al [25] and Martins et al [34] found that unloaded Zn-Al LDH did not cause mortality when tested on the clam Ruditapes phillipinarum and on M. edulis following 96 h of exposure. Avelelas et al [25] also demonstrated the inertness of LDH against the diatom Phaeodactylum tricornutum and the green unicellular alga Tetraselmis chuii.…”
Section: Unloaded Nanocarriers Ldh and Sincmentioning
confidence: 99%
“…Nanomaterials are highly valued by the petroleum industry because of their unique structure and excellent properties, and have been reported in many applications, such as drilling engineering, enhanced oil recovery, and anticorrosion materials . Carbon nanotubes (CNTs) are significant nanomaterials with excellent mechanical, electrical, and chemical properties, which are seamless hollow microtubules made of single or multiple layers of graphite sheets curled around a central axis at a certain spiral angle .…”
Section: Introductionmentioning
confidence: 99%